Shame, guilt, HIV and AIDS in rural communities : religion and health - Buys, P. J. (Practical Theology in South Africa = Praktiese Teologie in Suid-Afrika, 2008)
One of the most challenging issues in dealing with HIV and AIDS is breaking through the stigmas surrounding the disease. This article wants to contribute to the present discussion by investigating the relationship between shame and guilt and HIV and AIDS stigmatisation with specific reference to a rural community in South Africa. This will be done by looking at key features of the African worldview and culture and how it manifests in community attitudes towards people living with AIDS (PLWA). The influence of prevailing beliefs in witchcraft and the way it aggravates the experience of shame and suffering of stigmatisation by people infected and affected by HIV will also be highlighted. Approaches to Christian HIV and AIDS counselling and intervention has to be contextualised to be culturally sensitive and relevant. At the same time a Christian approach to HIV and AIDS intervention may be enriched and become more holistic in unveiling the aspects of the Christian Gospel dealing with God's merciful covering of the shame of his children and Christ having triumphed over and disarmed all spiritual powers and authorities.
Paid